Design Research: The Idiot’s Role in the ‘Smart’ Home - Delfina Fantini Van Ditmar (Diseña, 2018)
Through optimization and efficiency, Internet of Things (IoT) technology promises to make our cities, our houses and our bodies ‘smarter’. In the context of the growing industry of the ‘smart’ home, through a practice-based design research, I carried an investigation based on the conceptual figure of the ‘IdIoT’. Through this image we seek to interrogate this reality, slow down its assumptions and reflect on the epistemological processes involved in technology. In response to the rapid growth and accelerating commercialization of the Internet of Things, the intervention generated a series of questions on the eventualities of the process of algorithmization of our domestic life. By problematizing the ambiguities of technology, it was possible to observe how the algorithmic logic presents a series of controversies around the apparent neutrality of ‘smartness’.